The Influence of Successor Knowledge and Successor Willingness on Innovation Capability with Absorptive Capacity Mediation Variables and Moderating Variables Perception on Leader's Approval - Indahyati Dwi Astuti (Universitas Ciputra Surabaya, 2021)
This study aims to examine the effect of successor knowledge and successor willingness on innovation capability of family companies with absorptive capacity as a mediating variable and perception on leader‘s approval as a moderating variable. This study uses quantitative methods using SmartPLS for data processing. The number of respondents in this study were 113 family company successors who were selected using purposive sampling method. The results show that successor knowledge has no significant effect on innovation capability of family companies, successor willingness and absorptive capacity has a significant positive effect on innovation capability of family companies, absorptive capacity fully mediates the effect of successor knowledge on innovation capability of family companies, and the variable perception on leader‘s approval moderates the significant effect of successor willingness to innovation capability of family companies.